1991
DOI: 10.1088/0022-3727/24/4/018
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated depolarization current of a ferroelectric phase of 60:40 VDF/TrFE copolymer

Abstract: The authors have developed a model for explaining the thermally stimulated depolarization current obtained for a ferroelectric 60:40 mol.% VDF/TrFe (vinylidene fluoride-trifluoroethylene) copolymer, combining a slow process with a fast one. Initially the polarization decays slowly due to either the thermal depolarization of dipolar units originating in the beta -phase crystallites or the variation of the pyroelectric current. Subsequently the decay is accelerated and eventually brought to an end by the ferroel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This region of the TSC spectra was also studied by Neto et al 87 and Faria et al 31,87 who have found a peak which was shifted to higher temperatures with increasing TrFE content. Both authors concluded, that this relaxation is related to a ferroelectric to paraelectric transition.…”
Section: Effect Of Stable Ferroelectric Polarization On Thermally Stisupporting
confidence: 61%
“…This region of the TSC spectra was also studied by Neto et al 87 and Faria et al 31,87 who have found a peak which was shifted to higher temperatures with increasing TrFE content. Both authors concluded, that this relaxation is related to a ferroelectric to paraelectric transition.…”
Section: Effect Of Stable Ferroelectric Polarization On Thermally Stisupporting
confidence: 61%
“…It was found that the sample with higher α-Al(OH) 3 content was strongly affected by water immersion [333]. Table 5 Fit parameters for the α, β, γ, and δ relaxations in Vectra B950 for extruded samples [325] Parameter α a β γ δ Neto et al [334] developed a model for explaining the TSDC data for a ferroelectric 60:40 mol% VDF/TrFe (vinylidene fluoride-trifluoroethylene) copolymer, combining slow and fast processes. Initially the polarisation decays slowly, due to either thermal depolarisation of dipolar units originating in the betaphase crystallites, or variation of the pyroelectric current.…”
Section: -330 K) the Authorsmentioning
confidence: 99%
“…However, P(VDF-TrFE) clearly shows the Curie temperature near 390 K. 30,31) It has been reported that molecular conformation and spontaneous polarization are destroyed by applying heat above the Curie temperature in thermally stimulated current measurements. 32) Therefore, the pyroelectric characteristics of P(VDF-TrFE) films deteriorated because the depolarization occurred owing to the ferroelectric-paraelectric phase transition caused by heating at 398 K. Based on the above, VDF oligomers are superior to P(VDF-TrFE) in terms of thermal stability. Figure 5 shows the frequency dependence of the voltage sensitivity of the sensors.…”
Section: Resultsmentioning
confidence: 99%